'We should tax sex workers to fund subsidies for families': shifting affective registers and enduring (sexual) norms in the Italian Northern League's approach to prostitution. Issue 3 (2nd September 2019) - Crowhurst, Isabel
ABSTRACT: This paper explores changes in the emotional and affective repertoires mobilized by the Northern League, a radical right-wing populist party in Italy, to justify its recent prostitution policy proposal. Having dispensed to alarge extent with the punitive and fearful rhetoric against migrant prostitution that characterized its previous campaigns, under its new leader the Northern League has been calling for the regulation of prostitution and for its profitable taxation. The measures proposed, far from being non-moralistic and ideologically neutral, as they are presented, reinforce awell-established normative dichotomy between potentially dangerous individuals and the supposedly wholesome family.